4CPS-118 Real clinical impact of drug–drug interactions of immunosuppressants in transplant patients. (24th March 2020) - Gago-Sanchez, AI; Cardenas, M; Aumente, MD; Font, P; Del Prado, JR; Calleja, MA
Abstract : Background and importance: The risk of drug interactions in transplant patients is extremely high as they are polymedicated. The characteristics of immunosuppressants constitute an added risk. There are many potential drug–drug interactions (DDIs) but it would be interesting to know which ones are real and have clinical outcomes. Aim and objectives: The main objective of the study was to determine the prevalence of real DDIs between immunosuppressants and other drugs in transplant patients. Secondary objectives were to evaluate clinical impact, categorise the type of DDIs, identify drugs involved and propose alternative therapeutic strategies. Material and methods: A prospective, observational 1 year study (February 2018 to February 2019) was conducted at a third level hospital, including all new transplanted patients. DDIs were detected by a computer application. To determine real clinical DDIs, patient medical records were reviewed, looking for data on monitoring blood concentrations of immunosuppressive drugs and adverse drug events (ADEs) caused by DDIs. DDIs were classified in C, D or X according to the Lexi interact score (C=monitor therapy, D=consider therapy modification, X=avoid combination). The clinical importance of the real DDIs was expressed in terms of patient outcomes: percentage of patients with ADEs due to real DDIs. Data were analysed using SPSS V.17.0 (Chicago, Illinois, USA). Results: A total of 309 transplant patients were included with a mean age of 52±14 years (13–79) and 69.9% were men. The prevalence of real DDIs was 21.68%. The number of real DDIs between immunosuppressants and other drugs was 71. The largest type of real DDIs was category D (52 (73.23%)). Immunosuppressive drugs administered with antifungal azoles and tacrolimus with nifedipine had a great clinical impact due to the fluctuation in trough immunosuppressant blood concentrations (C0 ) of the immunosuppressants. The most common clinical outcomes were nephrotoxicity (12%), hyperkalaemia (10%) and hypertension (5%). Suggestions to avoid D and X for real DDIs included: immunosuppressant dose change, consider therapy modification and using paracetamol instead of non-steroidal anti-inflammatory drugs. A statistically significant linear correlation was detected between number of prescribed drugs and real and clinically important DDIs. Conclusion and relevance: There are many potential interactions described in the literature but only a small percentage have been proved to be real DDIs, based on patient outcomes, which were detected by determining the variations in C0 of immunosuppressants and ADEs caused by DDIs. Few patients suffered ADEs due to the close pharmacokinetic monitoring of immunosuppressants. The results allow us to identify the pharmacological groups that caused real DDIs. References and/or acknowledgements: No conflict of interest.